Opportunities for Using Green Bonds to Finance Environmental Projects in Developing Countries: Experience of the Republic of Kazakhstan - NURGALIYEVA, Aliya Miyazhdenovna; KAZBEKOVA, Zhanar Shamilovna; BOKENCHINA, Laura Kurymbaevna; BEKNIYAZOVA, Dana; BOKENCHIN, Kazbek Kuandykovich (Journal of Environmental Management and Tourism, 2022)
Sustainable business development based on environmental, social, and governance principles is one of the leading trends in the financial and global community. The introduction of environmental, social, and governance principles is intended to facilitate the implementation of countries’ pledges under the Paris Agreement on Climate and the achievement of the UN Sustainable Development Goals. In 2015, the Republic of Kazakhstan committed to following sustainable development goals, which made the principles of a sustainable and green economy a national priority of the 2050 Strategy. The study aims to identify the opportunities to use green bonds in Kazakhstan so as to increase the effectiveness of territorial management and the development of environmental projects. Proceeding from an expert survey, the study establishes arguments in favor of developing green bonds for the implementation of environmental projects in Kazakhstan, outlines the main hindrances to the advance of green bonds in the country, and lists the conditions required for further proliferation of the use of green bonds. The authors argue that the active use of green bonds can be facilitated by knowledge exchange, capacity building, and state support (especially in analyzing the economy of Kazakhstan) for the development of the market for green bonds, as well as state encouragement of private investors to green investment .